The role of users of accounting information in achieving customer satisfaction in the use of Lean accounting )Practical study in industrial companies registered in the stock market - Hayder Abbas Alatar; Azdhar Abdalah Zamil; Waad Hadi Abd (Journal of Madenat Alelem University College, 2019)
This study aimed mainly at the role of accounting users (Internal users and External users) in achieving customer satisfaction in the use of good accounting, as well as the relationship between the application of accounting tools and users of accounting information in achieving customer satisfaction by providing them with the product or service by Industrial Companies.                       In order to achieve the objectives of the study, the researchers used the analytical descriptive method by preparing the survey questionnaire prepared by some of the professors of the Faculty of Management and Economics at the universities of Qadisiya and Muthanna. The questionnaire was distributed to some workers in the industrial companies registered in the stock market The number of (5) companies, and distributed (65) form and returned (59) form, or 91%, has been conducted statistical analysis necessary to achieve the hypotheses of the study .                                                The study reached a number of results, the most important of which is that the registered companies in the stock market are interested in developing their activities through continuous improvement of their operations and production activities by follow up by the board of directors as well as investors, shareholders and lenders in order to provide the best services to the bank. Customer is affected by the extent to which accounting tools are used by users of accounting information.                               Therefore, the study recommends that the industrial companies registered in the stock market study the market and internal and external factors affecting the behavior of the customer before the introduction of any product or service, as well as the need for professional accounting associations represented by the Association of Accountants and the Association of Accountants and Auditors to establish specialized training courses and workshops in the industrial sector and establish Conferences and scientific seminars to identify the extent and importance of using accounting tools.